The Effect Of Endorphin Massage On The Intensity Of Dysmenorrhea In Adolescents Studying Social Sciences At Pasir Pengaraian University - Andria; Sisi Rahmadani; Elvira Junita; Nana Aldriana (International Journal of Health Engineering and Technology, 2025)
Menstruation is a natural process that occurs in women every month as a sign that the body is in the process of preparing for pregnancy. However, not a few teenagers experience disorders in their menstruation, one of which is dysmenorrhea. Disrupting daily activities due to the pain they feel. Based on data from the Rokan Hulu Health Office in 2019, it was found that the prevalence of anxiety reached 4.3% (4,936 people), and 59.5% of teenagers experienced dysmenorrhea. The incidence of dysmenorrhea in Riau, which has been studied in adolescent girls (age range 15-16 years) in Bangko District, Rokan Hilir Regency, found a prevalence of dysmenorrhea of 95.7%. Treatment of dysmenorrhea can be overcome with non-pharmacological methods to reduce dysmenorrhea pain, one of which is Endorphin Massage. This type of research is Quantitative with a pre-experimental research design with a pretest and posttest design approach using the NRS observation sheet. The population of this study was students of the Social Studies education study program at Pasir Pengaraian University, with a sample of 20 female students. The sampling technique was purposive sampling. The data analysis used univariate and bivariate methods. From the results of the study, it is known that the univariate analysis obtained an average pretest of 3.75 with a standard deviation of 1.165. The average posttest was 2.10 with a standard deviation of 1.021. This shows that the mean posttest value is smaller than the mean pretest value. The results of the bivariate analysis using the T-Test obtained a p-value of 0.000 (p <0.05). This indicates that there is a significant difference in the average intensity of dysmenorrhea before and after the administration of endorphin massage in female students of the Social Studies Education Study Program at Pasir Pengaraian University